Anatomy of septocutaneous blood vessels of the anterior forearm - Darko Jović; Mirza Bišćević; Milan Milisavljevic; Zoran Aleksić; Milica Jakovljević; Nevena Tešović; Mićo Kremenović (Medicinski glasnik, 2021)
Aim: To measure a calibre of radial and ulnar septocutaneous perforators at the anterior forearm, and to count its number in proximal, middle and distal thirds. Methods: The study was conducted on 50 fresh amputated forearms (trauma, tumours) in the period between January 2012 and December 2021. Forearms were collected from several hospitals in Belgrade, and analysed at the Institute of Anatomy, Medical School, University of Belgrade, Serbia. Injection of ink-gelatin and fine dissection of autopsy material was performed on 30 forearms, and corrosion method with injecting methyl methacrylate for 3D analysis on the other 20 forearms. Results: A mean calibre of septocutaneous perforators on the radial artery was 0.53±0.46 mm (0.2-0.85). Averagely, there were 8.1 radial artery septocutaneous perforators - two perforators on the proximal third, 3.7 on the middle third, and 2.7 on the distal third. The mean calibre of ulnar artery perforators was 0.65±0.35 mm (0.18-1.8). The average number of septocutaneous perforators of the ulnar artery was 5.6; 1.2 on the proximal third, two on the middle third, and 2.2 on distal third. Conclusion: Determination of the origin, calibre and spreading directions of the arterial septocutaneous perforators on the anterior forearm provide quantification of data about arborisation of radial and ulnar septocutaneous perforators at the anterior forearm. Clinical relevance of those anatomical data is in defining of safe locations and dimensions of forearm fasciocutaneous flaps in plastic surgery.
Keywords: flap; perforator; radial artery; ulnar artery